Atlas der Abwesenheit Kameruns Kulturerbe in Deutschland - Kollektiv, Autor:innen (Reimer Verlag, 2023)
More than 40,000 objects from Cameroon are now kept in public museums in the Federal Republic of Germany - the largest stock worldwide. For the first time, this invisible presence of Cameroon in German museums is traced, using numerous maps, charts and graphics.